PENDIDIKAN WANITA MUSLIMAH DALAM ILMU FIQIH - Bibi Ghoniyah; Eli Masnawati (As-Sulthan Journal of Education, 2025)
This study aims to describe Muslim women in the field of Islamic jurisprudence. This study uses a qualitative approach with content analysis. Data collection was conducted by documenting several documents relevant to the research topic. Data analysis was carried out through data collection, data condensation, data presentation, and drawing conclusions/verification. The results of this study indicate that Muslim women have specific laws and regulations discussed in Islamic jurisprudence that regulate their religious, social, and personal lives. A woman's private parts must be covered with loose clothing that does not reveal the curves of the body to maintain honor and avoid slander. During worship, Muslim women are not required to perform Friday prayers and are not permitted to lead prayers for men. Issues of menstruation, postpartum bleeding, and istihadhah also receive special attention, including the provision on whether a woman may attend a gathering of knowledge in the mosque while menstruating. Family rules are also discussed, for example regarding the guardianship of marriage, which is mandatory in a woman's marriage contract. All of these provisions demonstrate the sharia's attention to the protection, honor, and religious obligations of Muslim women. Sharia education is obligatory for Muslim women to understand the laws of women's jurisprudence and apply them in their daily lives. Women play a vital role in society, particularly in da'wah (Islamic outreach), provided they protect themselves from slander and avoid sexual intercourse with non-mahram men.